Have the Guests Perceived Superior Value? - Levyda Levyda (Bina Nusantara University, 2017)
This research aimed to describe guests’ perceived value by using a multidimensional approach. From previous research, guests’ perceived value consisted of some functional value, emotional value, and social value. Based on guest experience, and functional value consisted of physical evidence, guest room, food and beverage, hotel staff, and price. This research was conducted in four-star hotels in Jakarta. The respondents were the guests who had stayed in four-star hotels. The number of the respondent was 405. The data were obtained by using self-administered questionnaires. This research shows that guests have not perceived superior value. Some of the values and the necessary efforts need to be improved.